Collaborative Web Hosting Challenges and Research Directions - Ahmed, Reaz; Boutaba , Raouf (SpringerBriefs in Computer Science, 2014)
This brief presents a peer-to-peer (P2P) web-hosting infrastructure (named pWeb) that can transform networked, home-entertainment devices into lightweight collaborating Web servers for persistently storing and serving multimedia and web content. The issues addressed include ensuring content availability, Plexus routing and indexing, naming schemes, web ID, collaborative web search, network architecture and content indexing. In pWeb, user-generated voluminous multimedia content is proactively uploaded to a nearby network location (preferably within the same LAN or at least, within the same ISP) and a structured P2P mechanism ensures Internet accessibility by tracking the original content and its replicas. This new paradigm of information management strives to provide low or no-cost cloud storage and entices the end users to upload voluminous multimedia content to the cloud data centers. However, it leads to difficulties in privacy, network architecture and content availability. Concise and practical, this brief examines the benefits and pitfalls of the pWeb web-hosting infrastructure. It is designed for professionals and practitioners working on P2P and web management and is also a useful resource for advanced-level students studying networks or multimedia.